Anemia em gestantes: avaliação das usuárias das unidades básicas de saúde do Município de Cabedelo-Paraíba - Quintans, Alana Moura (2011)
Anemia is one of the most common nutritional worldwide deficiency, and more prevalent in children, adolescents, pregnant women and elderly population. The present study determined the prevalence of anemia in pregnant women, the relevant socioeconomic and nutritional status. Was conducted an observational cross sectional study with 130 pregnant women carefully followed during the pre natal stages at the public service in the city of Cabedelo-PB. Was also conducted an interview with questions dealing with the pregnancy, their socioeconomic surroundings and an anthropometric evaluation. The biochemical data were gathered through the medical records. The pregnant women with levels of hemoglobin less than 11g/dl were considered anemic. In order to conduct the necessary statistical test, was used the version 15.0 of SPSS (Statistical Package for the Social Sciences). Was used the 5% level of significance on all the statistical tests conducted. We observed the prevalence of anemia in 17.7% with an average hemoglobin and hematocrit levels of 12.28±1.56 g/dl and 37.96±5% respectively. Was used the T-test with equal variances, T-test with unequal variances, t-Student test, Mc-Nemar the Chi-square test and exact Fisher test. The highest prevalence was observed in the youngest group (≤ 34 years old), those that studied until the high school (22,7%), those with monthly income of less or equal to minimum wage, and the pregnants who lives at the lowest economic levels (18,8%). The percentage of pregnant women with anemia was higher among those who took iron supplements as opposed to those who did not (22,2% x 7,5%), which was the only variable that presented a significant association to the targeted level (i.e. p < 0,05). It was concluded that even having found a slight prevalence, anemia still is a serious problem during pregnancy, and there is a need to expand reinforcements targeted at this population group.